Ecological Modernisation of the Tourism - Iulia Carmen Terryn (CES Working Papers, 2011)
The article examines the capacity of the Ecological Modernisation Theory (EMT) as a paradigm for environmental policy making within the tourism destinations to improve their sustainability, competitiveness and commercial success. To cope with the challenges and threats the tourism faces, of great importance is setting-up an innovative policy- making model, to bring new perspectives, interactions between stakeholders and policy instruments to balance the economic growth and environmental concerns. While the ecological modernisation within the tourism industry makes necessary the introduction of new technologies and management strategies at the company level to bring about economic and environmental benefits, the state needs new policy instruments and approaches to deal with these new paths. Policy making process and ecological restructuring of the tourism sector is analysed using as a tool the “policy network” analysis.
Keywords: 330; Environmental Governance; Sustainable Tourism; Ecological Modernisation; Environmental-oriented Innovation; Policy networks; Romania